Supercritical Resonance in a Strong Magnetic Field - Tumakov, D. A.; Maltsev, I. A.; Popov, R. V.; Shabaev, V. M. (Optics and spectroscopy, 2023)
The position and width of supercritical resonance of one-electron ion in presence of a strong magnetic field are calculated. The influence of the magnetic field on the supercritical resonance parameters is investigated.